ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA DALAM ASPEK HUKUM INDONESIA - Lalu Muhammad Faisal (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2025)
Dispute is an effort to end the conflict or disputes that occur in society. This study uses qualitative with the research method used is the Descriptive research method. Qualitative descriptive analysis method. The results of the study show that the results of this study indicate that if a dispute occurs in the legal perspective in Indonesia, the parties want the most beneficial dispute resolution mechanism between the two parties. One of the choices of dispute resolution mechanisms is through arbitration. Arbitration has several advantages of dispute resolution through Alternative Dispute Resolution (ADR) is that the settlement is informal, which resolves the disputes of the parties themselves, the settlement period is short, the cost is low, the rules of evidence are not necessary, the settlement process is confidential, the relationship between the parties